Influence of Employers on Employees’ Family Decisions: Perspective of Employees of Russian Companies - Shubat, Oksana; Latushkin, Victor (Journal of Population and Social Studies [JPSS], 2025)
Addressing Russia’s negative demographic trends requires the formulation of novel and more effective policy measures. One measure actively implemented in Russia in recent years involves engaging businesses in addressing demographic issues through corporate demographic policies. This study aims to assess the potential influence of employers on employees’ family decisions by analyzing employees’ perceptions of that influence. Our research is based on a survey conducted across 15 regions of Russia. The results indicate that the vast majority of employees acknowledge that companies have moral obligations and should provide targeted support to employees with children. We propose an index of employers’ positive influence on employees’ family decisions, which shows that employees are moderately optimistic about that influence. Differences in this index were identified and analyzed among employee groups. Directions for future research are also suggested. The contributions of this study are both theoretical and empirical in nature. While the theoretical contribution addresses the development of the scholarly debate on the theory of the corporation as a moral person, the empirical contribution comprises a set of findings that facilitate the development of more effective corporate demographic policies.